Physical geology: exploring the earth - James S Monroe; Wicander, Reed (New York Wadsworth Publishing Company, 1998)
An overview of the physical aspects of the Earth's processes, above and below the surface, this text focuses on plate tectonics and the role that shifting plates have on the Earth's dynamic systems. The text also integrates environmental and economic geology themes throughout.
Keywords: Earth sciences and geology